Meta-Synthesis of Metacognition’s Role in Enhancing Mathematical Critical Thinking - Dimas Ghulam Istiqlal; Bambang Eko Susilo; Scolastika Mariani; Isnaini Rosyida (EduMa: Mathematics education learning and teaching, 2025)
This study aims to analyze and synthesize various research findings on the role of metacognition in developing students’ mathematical critical thinking skills. The method employed is a qualitative meta-synthesis using a systematic literature review approach on six published articles from 2020 to 2025 that are relevant to metacognition and critical thinking in mathematics learning. The analysis was conducted through thematic coding and cross-study interpretation to identify patterns, distinctions, and theoretical development directions. The synthesis results indicate that metacognition functions as a regulatory mechanism of intellectual awareness, guiding students to plan, monitor, and evaluate their thinking processes reflectively. The relationship between metacognition and critical thinking is reciprocal and hierarchical: metacognition serves as the foundation for critical thinking, while critical thinking reinforces metacognitive awareness through continuous reflection. These findings highlight a paradigm shift from metacognition as a teaching strategy to metacognition as a cognitive architecture. This study recommends the development of a conceptual model of the metacognitive–critical thinking cycle within mathematics learning contexts that are adaptive to students’ cognitive and cultural characteristics.